New Car price prediction model using AI before launch: Forward selection Regression - Vaseem, Mohd; Grover, Amandeep Singh; Amjad, Akhtarul Islam (International Journal of Computer Sciences and Engineering, 2026)
It is very important to predict car price before launching it in the market. In the research, regression models are developed to predict the price of the car. Three models have been developed in the research paper: Backward Elimination, Backward Elimination with VIF, and forward selection. The data is taken from Kaggle. The most important factors are decided by correlating other variables with the car price. A linear regression model is finally developed, with engine size as the most influencing factor, the type of driver as the second influencing factor, and the type of the car body as the third influencing factor. Linear regression model predicts the car price with good model accuracy. The exploratory data analysis is done to know about the data set. The variables having variance influence factor r more than ten are omitted to avoid the problem of multicollinearity. The first model developed is forward selection, in which engine size is used to build the first regression model having a single variable. The value of adjusted R2 is 0.764, and the aim is to increase the value of this factor, and all the coefficients in this model are statistically significant. The second variable included is the type of carburetor (2bbl) that is incorporated in the model, and a regression model is developed. The adjusted R2 is 0.778 and all the coefficients are statistically significant. The third regression model is developed by incorporating types of the drive (Reverse drive), and the value of adjusted R2 is 0.802, and all the coefficients are statistically significant. Further, it was tried by the hit and trial method incorporated the other variables in the model to increagression to predict the price of the car as it has less omitted variables bias.